VEGF blockade enhances the antitumor effect of BRAFV600E inhibition - Valentina Comunanza; Davide Corà; Francesca Orso; Francesca Maria Consonni; Emanuele Middonti; Federica Di Nicolantonio; Anton Buzdin; Antonio Sica; Enzo Medico; Dario Sangiolo; Daniela Taverna; Federico Bussolino (EMBO Molecular Medicine)
Abstract The development of resistance remains a major obstacle to long‐term disease control in cancer patients treated with targeted therapies. In BRAF‐mutant mouse models, we demonstrate that although targeted inhibition of either BRAF or VEGF initially suppresses the growth of BRAF‐mutant tumors, combined inhibition of both pathways results in apoptosis, long‐lasting tumor responses, reduction in lung colonization, and delayed onset of acquired resistance to the BRAF inhibitor PLX4720. As well as inducing tumor vascular normalization and ameliorating hypoxia, this approach induces remodeling of the extracellular matrix, infiltration of macrophages with an M1‐like phenotype, and reduction in cancer‐associated fibroblasts. At the molecular level, this therapeutic regimen results in a de novo transcriptional signature, which sustains and explains the observed efficacy with regard to cancer progression. Collectively, our findings offer new biological rationales for the management of clinical resistance to BRAF inhibitors based on the combination between BRAFV600E inhibitors with anti‐angiogenic regimens.